1995
DOI: 10.1002/rcm.1290091103
|View full text |Cite
|
Sign up to set email alerts
|

Study of water–cryoprotector mixtures by low temperature fast‐atom bombardment mass spectrometry

Abstract: Frozen solutions of a cryoprotector, glycerol, in water were studied by low temperature fast-atom bombardment mass spectrometry in the temperature range from -196" to 0 "C. Strong dependence of the mass spectral pattern on the water-glycerol ratio and temperature of the sample was observed. The evolution of mass spectra of the frozen 2000: 1 water-glycerol mixture with increase of the sample temperature is reproducible: in the lower portion of the temperature range (-196" to -120°C) the spectra contain a set o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

1998
1998
2003
2003

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(37 citation statements)
references
References 21 publications
2
35
0
Order By: Relevance
“…[77][78][79] It was to the author's greatest disappointment when it appeared impossible to produce hydrate clusters of a rather wide choice of organic molecules whose water solutions were tested under LT-FAB conditions. 45,46 This observation seemed to contradict some accepted notions on the mechanisms of secondary ion formation, in particular those concerning the intense mixing of all components of the sample in the zone excited by bombarding particle and formation of mixed clusters in chains of ion-molecule reactions. 16,25,67 Deeper consideration of these models, however, revealed that they were developed for objects of homogeneous structure: liquid solutions in the case of FAB and thin films in the case of organic SIMS.…”
Section: Model For Interpretation Of the Lt-fab Mass Spectramentioning
confidence: 85%
See 4 more Smart Citations
“…[77][78][79] It was to the author's greatest disappointment when it appeared impossible to produce hydrate clusters of a rather wide choice of organic molecules whose water solutions were tested under LT-FAB conditions. 45,46 This observation seemed to contradict some accepted notions on the mechanisms of secondary ion formation, in particular those concerning the intense mixing of all components of the sample in the zone excited by bombarding particle and formation of mixed clusters in chains of ion-molecule reactions. 16,25,67 Deeper consideration of these models, however, revealed that they were developed for objects of homogeneous structure: liquid solutions in the case of FAB and thin films in the case of organic SIMS.…”
Section: Model For Interpretation Of the Lt-fab Mass Spectramentioning
confidence: 85%
“…48 The investigation of cluster sputtering from ice is of interest for space, atmospheric and ecological research. 53,70,71 LT-FAB/SIMS studies were extended to organic compounds (mainly volatile solvents): glycerol, 21,[24][25][26]28 primary alcohols, 7,20,24,25 glycols 21 and some others. [22][23][24]27 The main observation with organic compounds was the existence of a strong dependence of the LT mass spectrum pattern and quality on the temperature of the sample.…”
Section: Applications Of Lt-fab/sims In Chemistry and Physicsmentioning
confidence: 99%
See 3 more Smart Citations